VERIFIKASI ANALISA KADAR LOGAM TIMBAL (Pb) DALAM DARAH DAN GAMBARAN HEMATOLOGI DARAH PADA PETUGAS TAMBANG BATU BARA - Rosita, Betti; Sosmira, Eri (IAIN Batusangkar, 2017)
Verification is performed on a method to prove that the relevant laboratory is capable of testing by such method with valid results Validation of the results of the examination to be performed by laboratory personnel to reinforce and confirm that the method used in accordance with its use, such as in the use of wet digestion method with test equipment that supports the laboratory is an Atomic Absorption Spectrometer (AAS), principally for the analysis of metal content in blood samples. One of the metals that may be contaminated with blood are metal Plumbum (Pb) threats to health such as the circulatory system and the central nervous system of humans, other negative impacts caused that damage to the kidneys, anemia, liver and reproductive system of humans. This research is an experiment, The results showed the blood sample examination officer Bara stone mine average Pb content results are still below the threshold (NAB) is 0.292 mg / L in accordance with Kepmenkes No. 1406 2002 of <10 g / L of blood price 0.5996% precision (<2%), the accuracy of 104.55% (100% ± 15%), LOD and LOQ 0.0252982 0.007589946 ppm ppm for the validation of the results can be stated that the method of destruction wet for test equipment SSA fit for use and picture examination results of laboratory hematolgi blood samples showed the complete blood still in the normal range whereas when viewed in counts an increase in lymphocytes of 40% and 37% (normal 25-35%) and monocyte 6% (normally 2-4%) indicate that the blood of those officers already contain lead (Pb).